Lessons from a small country about the global obesity crisis - Yach Derek; Brownell Kelly D (BMC, 2006)
Abstract Developed countries had high obesity rates before the problem was taken seriously and hence the genesis must be seen in retrospect. Developing countries offer a clear view of causal factors but also opportunities for prevention, which must focus on both food and physical activity environments.